Hometown Conflict and Refugees' Integration Efforts - Cevat Giray Aksoy; Gaurav Khanna; Victoria Marino; Semih Tumen (Institute of Labor Economics (IZA), 2024)
How does violence in origin areas affect the educational outcomes of refugees in their destinations? Using administrative panel data, we find that heightened violence in the hometowns of Syrian students leads to improvements in their school outcomes in Türkiye. Turkish language and Math scores of refugee students improve, with larger impacts on Turkish scores. There is no impact on naturalized Syrian students. We observe positive spillovers on Turkish students. These findings suggest ongoing violence in refugee-origin areas reduces the prospect of returning home, and induces students to increase their integration effort by investing in education.
Keywords: J15; I21; I25; F51; O15; 330; conflict; forced migration; integration effort; return migration